(untitled) (Indian Journal of Animal Production and Management, 2015)
Present study interprets the perception of dairy farmers about the quality of multimedia modules developed for the purpose along with the constraints faced and suggestions voiced. The quality of multimedia modules were perceived with the help of the parameters related to attractiveness, holding interests, use of visuals and models, production skills and presentation skills. The results revealed that majority of the dairy farmers had perceived that, the quality of multimedia modules are good and found to be useful. But, lack of awareness was perceived as major constraint while using multimedia modules as information source. An awareness campaign at different places at regular intervals will certainly help out to promote such multimedia modules as information source and that can be effectively used for disseminating technologies on various dairy farming practices.